The impact of employees’ emotions on their job performance at Anchor yeast private limited Zimbabwe. - Zwangendaba, Brilliant (Midlands State University, 2017)
This study found that emotions have a significant impact on employee’s job performance thus supporting the need for emotion management in organisations. Various studies have proved that emotions have been ignored in organisations due to the perception that they are an irrational phenomenon that aims only to oppose the voice of reason. Due to their abstract nature, organisational leaders have chosen to ignore them. With a harsh economic environment in Zimbabwe, it can however be safe to assume that the perceived job insecurities resulting from the economic environment on the part of employees have elicited various emotions among employees thereby providing enough rationale to look into the possibility of these emotions playing a certain role in how employees perform.